The buffering effect of government subsidies on tourism enterprise performance based on uncertainty shock - Jinhua He; Bingbing Xue; Liling Chen; Fan Chen (Management System Engineering)
Abstract The study aims at revealing the impact of government subsidies on the relationship between uncertainty shock and tourism enterprise performance, as well as the influencing mechanism. Taking the public health emergency in 2019 as a quasi-natural experiment, this study selected 27 listed tourism enterprises in China from 2016 to 2022 as samples. Hypotheses were tested through Difference-in-Differences (DID) model and the Difference-in-Differences (DID) model and the Triple Difference-in-Differences (DDD) model. The study finds that government subsidies can significantly alleviate the inhibitory effect of uncertainty shocks on the performance of tourism enterprises. The mechanism analysis shows that government subsidies alleviate the negative effects of uncertainty shock on tourism enterprise performance by improving their risk-taking ability. Further analysis shows that government subsidies had a more significant supporting effect on non-state-owned enterprise and enterprises that did not receive continuous government subsidies.